THE USE OF VISUAL SOURCES IN HISTORICAL RESEARCH (ON THE EXAMPLE OF V.F. TIMM’S ILLUSTRATIONS) - Polcaeva, Fatimat Abdulnetifovna (History, Archeology and Ethnography of the Caucasus, 2019)
Visual sources, like many others, are an important part of historical research. At the same time, the potential of visual sources has not yet been fully disclosed. The high degree of risk of their application is explained by the fact that visual materials (especially drawn ones) can be extremely subjective. Moreover, the lack of a universal scheme for their critical analysis reduces the possibility of their use in a research. With the development of historical science and the emergence of a so-called “visual history”, the need for further development of methods for the critical analysis of visual sources and their subsequent use has been identified. The author analyzes two illustrations by the Russian artist V.F. Timma, published in the “Russkyi khudozhestvenyi listok” (Russian Art Leaflet): “Types of Dagestan” (№ 34, 1859) and “The Portrait of Shamil” (№ 32, 1859), from which ethnographic and historical data was obtained. Both illustrations were analyzed, and the revealed data were compared with the available ethnographic information. This made it possible to demonstrate the possibilities and benefits of using visual materials for verification and confirmation of information from written sources. The study also resulted in an approximate analytic scheme of visual material, guided by which the author worked with full-scale drawings.